The Effect of Insider Ownership, Current Ratio, and Return On Equity on Firm Value CSR with as a Moderating Variabel - Fathiyah, Siti (Inovbiz: Jurnal Inovasi Bisnis, 2024)
This study aimed to examine the influence of independent variables on the dependent variable and test moderating variables that can strengthen or weaken the relationship between independent variables and the dependent variable. The independent variables used in this study are Insider Ownership, Current Ratio, and Return On Equity, the dependent variable is Firm Value, and the moderating variable used is Corporate Social Responsibility. The sampling method employed is purposive sampling. The sample size in this study consists of 16 mining companies listed on the Indonesia Stock Exchange (BEI). The data used in this study are secondary data sourced from annual reports, financial statements, and sustainability reports of the companies. Hypothesis testing in this study utilizes Partial Least Square. The results indicate that Insider Ownership has a significant impact on Firm Value, while Current Ratio and ROE do not significantly influence Firm Value. CSR moderates the influence of Insider Ownership on Firm Value, whereas CSR does not moderate or weaken the relationship between Current Ratio and ROE with Firm Value.